Phases and excitations of active rod–bead mixtures: simulations and experiments. Issue 31 (12th May 2020) - Soni, Harsh; Kumar, Nitin; Nambisan, Jyothishraj; Gupta, Rahul Kumar; Sood, A. K.; Ramaswamy, Sriram
Abstract : We present large-scale simulations, supplemented by experiments, on flocking, banding and broken-symmetry excitations in a monolayer of polar rods and spherical beads, confined between horizontal plates and rendered active by vertical vibration. Abstract : We present a large-scale numerical study, supplemented by experimental observations, on a quasi-two-dimensional active system of polar rods and spherical beads confined between two horizontal plates and energised by vertical vibration. For a low rod concentration Φ r, our observations are consistent with a direct phase transition, as bead concentration Φ b is increased, from the isotropic phase to a homogeneous flock. For Φ r above a threshold value, an ordered band dense in both rods and beads occurs between the disordered phase and the homogeneous flock, in both experiments and simulations. Within the size ranges accessible, we observe only a single band, whose width increases with Φ r . Deep in the ordered state, we observe broken-symmetry "sound" modes and giant number fluctuations. The direction-dependent sound speeds and the scaling of fluctuations are consistent with the predictions of field theories of flocking; sound damping rates show departures from such theories, but the range of wavenumbers explored is modest. At very high densities, we see phase separation into rod-rich and bead-rich regions, both of which move coherently.